Operators, geometry and quanta methods of spectral geometry in quantum field theory - Fursaev, Dmitri; Vassilevich, Dmitri; SpringerLink (Online service). (Dordrecht New York Springer Science+Business Media B.V., 2011)
This book gives a detailed and self-contained introduction into the theory of spectral functions, with an emphasis on their applications to quantum field theory. All methods are illustrated with applications to specific physical problems from the forefront of current research, such as finite-temperature field theory, D-branes, quantum solitons and noncommutativity. In the first part of the book, necessary background information on differential geometry and quantization, including less standard material, is collected. The second part of the book contains a detailed description of main spectral functions and methods of their calculation. In the third part, the theory is applied to several examples (D-branes, quantum solitons, anomalies, noncommutativity). More than hundred exercises together with their solutions are included. This book addresses advanced graduate students and researchers in mathematical physics and in neighbouring areas with basic knowledge of quantum field theory and differential geometry. The aim is to prepare readers to use spectral functions in their own research, in particular in relation to heat kernels and zeta functions.
1Preface -- 2 Notation Index I The Basics: 3 Geometrical Background -- 4 Quantum fields II Spectral geometry: 5 Operators and their spectra -- 6 Spectral functions -- 7 Non-linear spectral problems -- 8 Anomalies and Index Theorem III Applications: 9 Effective action -- 10 Anomalies in quantum field theories -- 11 Vacuum energy -- 12 Open strings and Born-Infeld action -- 13 Noncommutative geometry and field theory IV Problem solving: 14 Solutions to exercises.
Electronic reproduction.
Keywords: Spectral geometry; Quantum field theory; Electronic books